1999
DOI: 10.1111/j.1545-5300.1999.00117.x
|View full text |Cite
|
Sign up to set email alerts
|

Sibling Accounts of Attention Deficit Hyperactivity Disorder (ADHD)

Abstract: The goal of this research was to generate a description of how siblings in families with attention deficit hyperactivity disorder (ADHD) children experienced and lived with this chronic behavioral disorder. Interview and diary data from 11 families (N = 43) were analyzed using the constant comparative method. Data analysis revealed that siblings felt victimized by their ADHD sibling and that their experience of victimization was often minimized or overlooked in the family. Findings suggest that there is a need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
80
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 24 publications
(42 reference statements)
7
80
0
3
Order By: Relevance
“…In addition, Seligman and Darling (1989) found that anger, guilt, and resentment are frequently experienced by siblings of children with are ill and disabled. In qualitative interviews of siblings of children with ADHD, Kendall (1999) found that retaliatory aggression was a common phenomenon among these children. Research that focused on the siblings of children with visible disabilities may also provide an explanation for the higher levels of anger reported in this study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, Seligman and Darling (1989) found that anger, guilt, and resentment are frequently experienced by siblings of children with are ill and disabled. In qualitative interviews of siblings of children with ADHD, Kendall (1999) found that retaliatory aggression was a common phenomenon among these children. Research that focused on the siblings of children with visible disabilities may also provide an explanation for the higher levels of anger reported in this study.…”
Section: Discussionmentioning
confidence: 98%
“…Baldwin et al (1995) observed that siblings of aggressive children with ADHD are also more likely to manifest such aggressive behavior within the family system, thus providing further opportunities for conflict. Additionally, Kendall (1999) found that siblings often feel victimized by their ADHD siblings.…”
mentioning
confidence: 97%
“…Positive experiences include personal growth, enhanced family closeness, and increased empathy, responsibility, adaptability, problem-solving, and creativity [7][8][9][10][11][12]. Negative effects include experiencing worry, sorrow, fear, loss, jealousy, shame, anger, guilt, and resentment [3][4][5][6][7][8]. As a result, siblings' QOL may be impaired [13].…”
mentioning
confidence: 99%
“…The level of anxiety (both generalized and separation) is examined in the non-ADHD co-twin of a child with ADHD. Kendall (1999) emphasized that high anxiety is a significant issue for siblings of children with ADHD. Additionally, it is expected that the anxiety levels in a co-twin of a child with ADHD will be higher than that of a nontwin sibling, as twins are the same age and may often be in the same class, share the same peer group and be more easily compared with each other.…”
Section: Siblings Of An Adhd Childmentioning
confidence: 99%